Learning from implementation setbacks: Identifying and responding to contextual challenges. Issue 4 (26th September 2018) - Harrison, Michael I.; Grantham, Susan
Abstract: Introduction: We address organizational learning about implementation context during setbacks to primary care redesign in an ambulatory system. The redesign expanded care teams and added a medical assistant assigned administrative and coordination tasks. The redesign was expected to improve care efficiency, prevention, and continuity. In response to setbacks, redesign and system leaders used understanding of context to plan system‐wide changes, as well as program adjustments. Doing so enhanced the redesign's prospects and contributed to system learning. Methods: We conducted a 33‐month, mixed‐methods study. Qualitative data included quarterly calls with the redesign leaders and 63 activity log entries. There were three site visits; 73 interviews with practice leaders, providers, and medical assistants. Data analysis used categories from an implementation research framework; these were refined and then expanded inductively using log reports, debriefings with change leaders, and documents. Quantitative analysis used system operational data on chronic care, prevention, efficiency, productivity, and patient access. Results: Redesigned teams were not implemented as widely or rapidly as anticipated and did not deliver hoped‐for gains in operational metrics. Interviews reported that team redesign was leading to improvements in chronic care and prevention and eased provider burden. Besides making small adjustments to cope with setbacks, redesign and system leaders engaged in more thorough organizational learning. They examined contextual challenges underlying setbacks and posing risks to the delivery system as a whole. Their responses to challenges helped strengthen the redesign's prospects, improved the delivery system's position in its labor market, and helped the system prepare to meet emerging requirements for value‐based care and population health. Conclusions: This case points to benefits for both health care researchers and change practitioners of paying closer attention to how context affects implementation of organizational change, and to opportunities and conditions for learning from setbacks during change.